Detection of Mice DNA in Meatballs Using Real Time – PCR - Septiani, Triayu; Pendrianto, Pendrianto (Jurnal EnviScience (Environment Science), 2018)
Meat is one of perishable food and has the high of water content and protein content. Meatballs are processed food who are using meat as main ingredient and other ingredients, such tapioca flour, salt, pepper, and the other ingredients as food additives. Meatballs is the mostpopular because has tasty flavor, high protein content, especiallyessential amino acids.In Indonesia, until now there were still cases of counterfeiting of processed meat products. One of method is mixing the beef meat and other animalsmeat in the making process to reduce production costs, so that similar products can be obtained at a much lower cost. One common case is the mixing of beef meat with rat meat. This study aims to identify meatballs contaminated by rat meat. Meatball samples used do not have Halal certificate from LPPOM MUI. From the results of the study, obtained the green amplification curve with the highest peak showed positive control of rat DNA, followed by three other green curves from the sample that showed the occurrence of amplification, thus indicating samples positive containing rat DNA. In the positive sample, the rat DNA concentration in the sample is quite low which can be seen from the intensity of the peak produced on the amplification curve when compared with positive control. Keywords :DNA, Meat,Meatballs, Rat, RT – PCR